Study on the impact of thermal expansion on carbon fiber composite-aluminum alloy connections - GAO Yang; ZHOU Xiaochen; ZHOU Weixu; WANG Yanxiang; LIU Xiao; QIN Hao (机车电传动)
The coefficient of thermal expansion differs between carbon fiber composites and aluminum alloys to some extent, leading to varying degrees of deformation under changing service temperatures, which causes significant stress at their connections. Combining theoretical analysis and numerical simulation, this study examined the effect of varying thermal expansion coefficients on the connection performance between carbon fiber composites and aluminum alloys under typical vehicle operating conditions. The study considered the following environmental temperatures: atmospheric temperature at 23 °C, high temperature at 60 °C, and low temperature at -40 °C. The results show that under typical load conditions, both the tensile strain and compressive strain of the composites, as well as the stress in the aluminum alloys, reach their maximum values at the low temperature, while at the atmospheric temperature, these parameters reach their minimum values. At both high and low temperatures, the tensile and shear forces on the rivets increase compared to the states at the atmospheric temperature. Specifically, the rivets are more affected by shear forces at the high temperature and more affected by tensile forces at the low temperature.